Pendidikan Karakter Dalam Pembelajaran Matematika Di SD - Nuning Khamidah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Mathematics has an important role in various disciplines and advance the human intellect. Efforts to equip learners to be a master of science and technology, not enough if only concentrated on cognitive mastery. t is necessary also debriefing cultivation of character education for students in question. Planting through character education in learning mathematics, students are expected to practice good science in a balanced cognitive, affective and psikomorik. Keywords: education, character, learning, math.